2007
DOI: 10.1186/1471-2458-7-235
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the family nucleus on obesity in children from northeastern Brazil: a cross-sectional study

Abstract: Background: Obesity is considered to be caused by a combination of heredity and environmental factors with typical onset during childhood. The aim of this study was to identify family risk factors for the development of obesity in children from Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
13
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 26 publications
(25 reference statements)
8
13
0
3
Order By: Relevance
“…Moreover, one of the most important predictive factors of childhood overweight/obesity is parental (primarily maternal) overweight. This has been found in both industrialized (21, 34) and non-industrialized (28, 29, 73) countries.…”
Section: Psychosocial Risk Factorsmentioning
confidence: 83%
“…Moreover, one of the most important predictive factors of childhood overweight/obesity is parental (primarily maternal) overweight. This has been found in both industrialized (21, 34) and non-industrialized (28, 29, 73) countries.…”
Section: Psychosocial Risk Factorsmentioning
confidence: 83%
“…Others studies conducted by our group clearly showed that childhood obesity has high prevalence in developing countries [22] and leads to several cardio metabolic disturbances, such as increase in blood pressure [23,24] presence of fatty liver disease [25], IR [26], metabolic syndrome and subclinical inflammation [17]. Therefore, excessive weight is related to a preatherosclerosis status that starts early in life and is associated with increased mortality due to CVD [27].…”
Section: Discussionmentioning
confidence: 99%
“…Intrauterine growth may also influence the distribution of fat and lean tissue in the body and thus the proportion of fat to lean tissue for a particular BMI in childhood. 19,20 This, 14 i.e. countries with urban rich, urban poor and rural communities pursuing traditional ways of life, childhood overweight/obesity in affluent urban families may reach prevalences almost equivalent to those in North America whilst prevalences in the rural poor remain low.…”
Section: Defining Overweight/obesity In Childhoodmentioning
confidence: 99%